Ethnic Differences in Bone Health - Zengin, Ayse; Prentice, Ann; Ward, Kate Anna (Frontiers in Endocrinology, 2015)
There are differences in bone health between ethnic groups in both men and in women. Variations in body size and composition are likely to contribute to reported differences. Most studies report ethnic differences in areal bone mineral density (aBMD) which do not consistently parallel ethnic patterns in fracture rates. This suggests that other parameters beside aBMD should be considered when determining fracture risk between and within populations, including other aspects of bone strength: bone structure and microarchitecture as well muscle strength (mass, force generation, anatomy) and fat mass. We review what is known about differences in bone-densitometry derived outcomes between ethnic groups and the extent to which they account for the differences in fracture risk. Studies are included that were published primarily between 1994 – 2014. A ‘one size fits all approach’ should not be used to understand better ethnic differences in fracture risk.